Acidophilic actinobacteria synthesised silver nanoparticles showed remarkable activity against fungi‐causing superficial mycoses in humans. Issue 3 (16th December 2015) - Anasane, N.; Golińska, P.; Wypij, M.; Rathod, D.; Dahm, H.; Rai, M.
Summary: Superficial mycoses are limited to the most external part of the skin and hair and caused by Malassezia sp., Trichophyton sp. and Candida sp. We report extracellular biosynthesis of silver nanoparticles (AgNPs) by acidophilic actinobacteria (SF23, C9) and its in vitro antifungal activity against fungi‐causing superficial mycoses. The phylogenetic analysis based on the 16S rRNA gene sequence of strains SF23 and C9 showed that they are most closely related to Pilimelia columellifera subsp. pallida GU269552 T . The detection of AgNPs was confirmed by visual observation of colour changes from colourless to brown, and UV–vis spectrophotometer analysis, which showed peaks at 432 and 427 nm, respectively. These AgNPs were further characterised by nanoparticle tracking analysis (NTA), Zeta potential, Fourier‐transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The FTIR analysis exhibited the presence of proteins as capping agents. The TEM analysis revealed the formation of spherical and polydispersed nanoparticles in the size range of 4–36 nm and 8–60 nm, respectively. The biosynthesised AgNPs were screened against fungi‐causing superficial mycoses viz., Malassezia furfur, Trichophyton rubrum, Candida albicans and C. tropicalis . The highest antifungal activity of AgNPs from SF23 and C9 against T . rubrum and the least against M. furfur and C. albicans was observed as compared to other tested fungi. The biosynthesised AgNPs were found to be potential anti‐antifungal agent against fungi‐causing superficial mycoses.